Development of Army Synthetic Automotive Engine Oils for Arctic Service. - Lestz,Sidney J.; Bowen,Thomas C. (1975)
A three-phase program was conducted by the Army in order to obtain basic data required for the development of a new arctic engine oil (OEA) specification to replace the obsolete MIL-L-10295 sub-zero engine oil specification (OES). The first phase of the program involved the development and initial testing of improved arctic engine oils formulated using synthetic hydrocarbon or ester base stock materials. The second phase of the program involved field-testing of the improved oils, and the third phase covered definition of the performance requirements necessary for the new specification, MIL-L-46167 (OEA). This report covers the initial testing, development of the improved arctic engine oils, discussion relating to mixed fleet military test experience with the new lubricants, and laboratory testing of these new oils in standard oil test engines as well as in a specific military high-output diesel engine. Experience has shown these new synthetic lubricants are superior to the former mineral-based oils in ground-powered equipment and that they also function well as year-round hydraulic and power transmission lubricants.